A new approach in functionalization of carbon nanoparticles for optoelectronically relevant carbon dots and beyond. (January 2019) - Ren, Xianyan; Liang, Weixiong; Wang, Ping; Bunker, Christopher E.; Coleman, Montrez; Teisl, Lindsay Rose; Cao, Li; Sun, Ya-Ping
Abstract: Carbon dots (CDots), generally small carbon nanoparticles with surface passivation by a soft corona-like layer of mostly organic species, have been actively pursued for potential applications in optoelectronics, including various functions that have been served by some popular fullerene derivatives. For the preparation of CDots, chemical functionalization of pre-processed and selected small carbon nanoparticles by organic molecules, so far mostly molecules with primary and secondary amine groups, has been an effective method. In this study, carbon nanoparticles were functionalized by N -ethylcarbazole (NEC) under microwave-assisted reaction conditions for NEC-CDots, analogous but with advantages to the CDots of surface functionalization by poly( N -vinylcarbazole) (PVK, which holds a special place in optoelectronics). NEC molecules can apparently be activated under the reaction conditions for reactive functionalities such as radicals to bind to surface carbons of the nanoparticles, consistent with the observed high stability of NEC-CDots. These dots, likely with a unique surface passivation scheme, exhibited optical properties and photoinduced redox characteristics similar to those found in other high-performance CDots. The potentially broad applicability of the new functionalization approach is discussed, so are implications of the unique surface passivation of carbon nanoparticles by the carbazole moieties. Graphical abstract: Image